Imagens disruptivas da memória: a poética de uma exposição antimonumento - Lucas Ferreira de Vasconcellos (2022)
This research presents a case study on the Atlântico exhibition Vermelho by the artist, researcher and educator Rosana Paulino, which took place in 2017, inside the Padrão dos Descobrimentos, a historical monument located at banks of the Tagus River, in the city of Lisbon, in Portugal. In an interdisciplinary character, the work discusses to what extent Paulino's artistic praxis, which articulates different temporalities of images from the past, takes on a pedagogical and decolonial on the hegemonic meanings of history and its monumentalization in museum exhibition projects. In this way, it understands the processes of remaking collective memory as an important strategic device for disruption of contemporary art, contributing to an anti-monument poetics in contexts of extroversion of cultural heritage.